2021
DOI: 10.1172/jci.insight.143465
|View full text |Cite
|
Sign up to set email alerts
|

Reversible cardiac disease features in an inducible CUG repeat RNA–expressing mouse model of myotonic dystrophy

Abstract: In this study, we developed and characterized a transgenic mouse model for studying the cardiac pathogenesis of myotonic dystrophy type 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 73 publications
2
9
0
Order By: Relevance
“…Due to its size of 95bp, inclusion of exon 9 results in a frameshift that produces an alternative C-terminus in MBNL2, removing a PEST degradation domain in the C-terminus encoded by the mRNA that excludes exon 9. We also found that inclusion of Mbnl2 exon 6 and exon 9 and MBNL2 protein levels are significantly increased in our inducible DM1 heart mouse model (CUG960) that expresses an mRNA containing 960 CUG repeats in the context of human DMPK ( 25 ), indicating that the compensatory mechanism might also be active in DM1 tissues.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Due to its size of 95bp, inclusion of exon 9 results in a frameshift that produces an alternative C-terminus in MBNL2, removing a PEST degradation domain in the C-terminus encoded by the mRNA that excludes exon 9. We also found that inclusion of Mbnl2 exon 6 and exon 9 and MBNL2 protein levels are significantly increased in our inducible DM1 heart mouse model (CUG960) that expresses an mRNA containing 960 CUG repeats in the context of human DMPK ( 25 ), indicating that the compensatory mechanism might also be active in DM1 tissues.…”
Section: Introductionsupporting
confidence: 58%
“…Thus, we were curious to investigate if the compensatory mechanism also occurs in tissues expressing CUGexp RNA. To do so, we used a recently generated a dox-inducible DM1 heart mouse model (Figure 7A ), TREDT960I/MHCrtTA (CUG960), that expresses 960 interrupted CUG repeats in the context of human DMPK and recapitulates the electrophysiological and molecular cardiac features of DM1 ( 25 ). To test if the inclusion of Mbnl2 exon 6 and exon 9 and MBNL2 protein levels are increased in heart tissue from these mice, we induced the CUG960 RNA using 2 g dox/kg chow starting at postnatal day 1 and harvested the hearts at eight weeks of age.…”
Section: Resultsmentioning
confidence: 99%
“…RNA-Seq from heart samples in this model revealed gene expression and AS changes in ion transport genes associated with inherited cardiac conduction diseases, including a subset of genes involved in calcium handling. Consistent with the RNA-Seq results, calcium-handling defects were identified in atrial cardiomyocytes isolated from this model, potentially contributing to the observed arrhythmogenic phenotypes [62].…”
Section: Omics Studies In the Heartsupporting
confidence: 85%
“…Recently, a new mouse model has been reported, with inducible expression of human DMPK exons 11-15 carrying 960 interrupted CTG repeats in cardiomyocytes [62]. RNA-Seq from heart samples in this model revealed gene expression and AS changes in ion transport genes associated with inherited cardiac conduction diseases, including a subset of genes involved in calcium handling.…”
Section: Omics Studies In the Heartmentioning
confidence: 99%
“…Recently, another inducible/reversible mouse model of RNA toxicity in DM1 (TREDT960I) was reported from the Cooper lab, with cardiac specific expression of an RNA with exons 11–15 of DMPK with 960 interrupted CUGs [ 113 ]. These mice show RNA foci and a multitude of RNA splicing defects, decreased expression of connexin-40, and had prolongation of the QRS and QT c intervals, but did not show the prolongation of the PR interval, progressive heart block or sudden death seen in individuals with DM1.…”
Section: Mouse Models Of Rna Toxicity In Dm1 With Cardiac Phenotypesmentioning
confidence: 99%